Factors Influencing the Selection of Restaurant for Dining in Dhaka City of Bangladesh (Global Journal of Management and Business Research, 2018)
Eating outside the home became a new trend nowadays in Dhaka city of Bangladesh, and that has an impact on the restaurant industry of Dhaka. This is due to the increase in income and the changes in tastes and preference of the city dwellers. Hence, this study has been designed to identify the factors influencing the selection of restaurants by the Dhaka city dwellers. Both primary and secondary data were used to conduct this study. A structured questionnaire having five-point scale, one having strongly disagreed and five having strongly agreed used to conduct the survey. The data were analyzed using both descriptive and inferential statistics. Descriptive statistics were sued to descriptive the restaurants, and the variables of Dhaka city and inferential statistics were used to identify the relationship between the factors influencing the selection of the restaurants and the overall selection decision of the restaurant customers. Results show that the restaurant customers are influenced by five factors such as customer service, availability of variety and junk foods, maintenance of privacy, the brand name of the restaurant, and availability of ready-made food in Dhaka.
Keywords: customer service; availability of variety of foods; maintenance of privacy; brand name of the restaurant; availability of ready-made food